Box Design of Series Parallel Plug-in and Monitoring of LiFePO4 Battery Performance as Solar Panel Power Storage - Affandi, Faradina Virdania; Ahmad, Ilham Dhani; Abadi, Muhammad Ridha; Desideria, Raden Roro Wyne Ananda; Aji, Wahyu Waskito; Putri, Tika Erna (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2026)
The development of renewable energy, especially solar power, drives the need for efficient and safe energy storage systems. Lithium Iron Phosphate (LiFePO₄) battery are one of the main choices because they have stable characteristics, long service life, and are safe against high temperatures. This study aims to design a bateraiery container and a LiFePO₄ battery performance monitoring system as a power storage from solar panels. The container design considers thermal aspects, safety, and practicality of installation, while the monitoring system is built using an ESP32 microcontroller integrated with an ACS712 current sensor, a voltage sensor, and a DS18B20 temperature sensor to measure important bateraiery parameters. Tests were conducted to assess the performance of the monitoring system accuracy, bateraiery performance under charging and discharging conditions, a series-parallel plug-in connection system using an XT60 connector, and the effect of using a fan on the container at outdoor temperatures. The results show that the monitoring system has a current sensor error of 13.64%, a voltage sensor error of 1.01%, and a temperature sensor error of 4.92%. The reliability of the series-parallel plug-in connection system using XT60 connectors is considered good and works well. The cooling fan used has good usability for maintaining the battery temperature inside the container at outdoor temperatures.